Selective micellar electrokinetic chromatographic method for simultaneous determination of some pharmaceutical binary mixtures containing non-steroidal anti-inflammatory drugs - Michael E. El-Kommos; Niveen A. Mohamed; Ahmed F. Abdel Hakiem (Elsevier, 2013)
A simple and selective micellar electrokinetic chromatographic (MEKC) method has been developed for the analysis of five pharmaceutical binary mixtures containing three non-steroidal anti-inflammatory drugs (NSAIDs). The investigated mixtures were Ibuprofen (IP)âParacetamol (PC), Ibuprofen (IP)âChlorzoxazone (CZ), Ibuprofen (IP)âMethocarbamol (MC), Ketoprofen (KP)âChlorzoxazone (CZ) and Diclofenac sodium (DS)âLidocaine hydrochloride (LC). The separation was run for all mixtures using borate buffer (20Â mM, pH 9) containing 15% (v/v) methanol and 100Â mM sodium dodecyl sulphate (SDS) at 15Â kV and the components were detected at 214Â nm. Different factors affecting the electrophoretic mobility of the seven investigated drugs were studied and optimized. The method was validated according to international conference of harmonization (ICH) guidelines and United States pharmacopoeia (USP). The method was applied to the analysis of five pharmaceutical binary mixtures in their dosage forms. The results were compared with other reported high performance liquid chromatographic methods and no significant differences were observed. Keywords: Capillary electrophoresis, Micellar electrokinetic chromatographic method, Non-steroidal anti-inflammatory drugs, Pharmaceutical binary mixtures, Pharmaceutical analysis